Frequency‐specific alternations in the amplitude of low‐frequency fluctuations in schizophrenia. Issue 2 (5th November 2012) - Yu, Rongjun; Chien, Yi‐Ling; Wang, Hsiao‐Lan Sharon; Liu, Chih‐Min; Liu, Chen‐Chung; Hwang, Tzung‐Jeng; Hsieh, Ming H.; Hwu, Hai‐Gwo; Tseng, Wen‐Yih Isaac
<x xml:space="preserve">Abstract</x> Schizophrenia has been associated with abnormal task‐related brain activation in sensory and motor regions as well as social cognition network. Recently, two studies investigated temporal correlation between resting‐state functional magnetic resonance imaging (R‐fMRI) low‐frequency oscillations (LFOs) in schizophrenia but reported mixed results. This may be due to the different frequency bands used in these studies. Here we utilized R‐fMRI to measure the amplitude of low‐frequency fluctuations (ALFF) and fractional ALFF (fALFF) in three different frequency bands (slow‐5: 0.01–0.027 Hz; slow‐4: 0.027–0.08 Hz; and typical band: 0.01–0.08 Hz) in 69 patients with schizophrenia and 62 healthy controls. We showed that there were significant differences in ALFF/fALFF between the two bands (slow‐5 and slow‐4) in regions including basal ganglia, midbrain, and ventromedial prefrontal cortex. Importantly, we also identified significant interaction between frequency bands and groups in inferior occipital gyrus, precunus, and thalamus. The results suggest that the abnormalities of LFOs in schizophrenia is dependent on the frequency band and suggest that future studies should take the different frequency bands into account when measure intrinsic brain activity. Hum Brain Mapp 35:627–637, 2014. © 2012 Wiley Periodicals, Inc.